Modeling and Optimization of Teacher Innovativeness Enhancement Based on Technological Literacy and Organizational Support (A Study Using the POP-SDM Method on Permanent Teachers at Private Vocational School Foundations in West Jakarta) - M. Ardiansyah; Hardhienata Hardhienata; H. Soewarto; Suhendra Suhendra (Universitas Negeri Malang, 2025)
Abstract: This study examines the influence of digital literacy, transformational leadership, and organizational culture on teacher innovativeness in private vocational schools (SMK) in West Jakarta, involving 187 respondents. Utilizing PLS-SEM analysis and SITOREM method, the findings reveal that digital literacy exerts the strongest impact on teacher innovation (β=0.966, p